Disparitas Putusan dalam Pembatalan Penetapan Pengangkatan Anak (Adopsi) Oleh Orang Tua Angkat: Analisis Beberapa Putusan Pengadilan di Indonesia - Nur Fajriah, Kartika; Suhaidi; Suria Ningsih (JOM, 2025)
This study aims to analyze the causes of disparities in court rulings on petitions for the annulment of child adoption decrees and to examine the legal implications regarding the rights and obligations of parents towards their children in such annulment cases. This research employs a normative juridical approach, referring to legal norms through a literature study to obtain secondary data in the form of primary, secondary, and tertiary legal materials relevant to the issue under investigation. The study adopts a descriptive approach, with data collection conducted through a literature review of relevant regulations and legal materials. The data analysis method used is qualitative. The findings reveal that the disparities in court rulings on the annulment of child adoption decrees in Decision No. 130/Pdt.G/2017/PN.Jkt.Tim, Decision No. 83/PDT/2018/PT.DKI, and Decision No. 1210 K/Pdt/2019 are due to the absence of specific regulations governing the annulment of child adoption. Consequently, judges base their legal considerations on their respective interpretations, leading to inconsistencies in rulings for similar cases. This inconsistency indicates a lack of clear benchmarks in adjudicating child adoption annulment cases. Regarding the legal implications for parental rights and obligations in cases where the annulment of child adoption is rejected by the court, this study finds that the legal relationship between both parties remains unchanged from before the annulment petition was filed. The study concludes that adoptive parents seeking to annul an adoption decree may pursue legal remedies through the judiciary, provided they present legally justifiable reasons. Therefore, the establishment of specific regulations on the annulment of child adoption is necessary to provide judges with a clear legal framework for adjudicating similar cases in the future.